A case of bloodstream infection caused by Ruminococcus gnavus without gastrointestinal involvement - Tomoki Furutani; Hiroyuki Kitano; Kenichiro Ikeda; Satoshi Shirane; Yumiko Koba; Seiya Kashiyama; Hiroki Kitagawa; Kohei kobatake; Keisuke Hieda; Hiroki Ohge; Nobuyuki Hinata (Heliyon, 2023)
We report a case of bloodstream infection due to Ruminococcus gnavus (R. gnavus) associated with pelvic abscess in a 74-year-old female patient undergoing radiotherapy for cervical cancer. Gram staining of positive anaerobic blood cultures revealed short chains of gram-positive cocci. Matrix-assisted laser desorption ionization time-of-flight mass spectrometry was performed directly on the blood culture bottle, and 16S rRNA sequencing identified the bacterium as R. gnavus. There was no leakage from the sigmoid colon to rectum on enterography, and R. gnavus was not found in the culture of her pelvic abscess. After the administration of piperacillin/tazobactam, her condition markedly improved. This patient with R. gnavus infection demonstrated no gastrointestinal involvement, whereas past published cases reported diverticulitis or intestinal damage. It is possible that bacterial translocation of R. gnavus occurred from the gut microbiota, due to damage to the intestinal tract caused by radiation.